MAINTAINING OPTIMAL NUTRITION AND ENERGY BALANCE FOR BASKETBALL PLAYERS - Ashurova Ibotkhon Ilhomjon qizi (Modern American Journals, 2025)
Basketball is a sport that requires a high level of physical activity, and proper nutrition is essential for improving athletes' performance and preventing injuries. This article provides a comprehensive analysis of the principles of optimal nutrition for basketball players, strategies for maintaining energy balance, and the importance of macro and micronutrients in increasing physical fitness. In addition, the effects of meals taken before and after training and competition on the body, the importance of fluid balance, and electrolytes are also studied. The study offers practical recommendations for optimizing the energy balance of basketball players, based on the scientific foundations of modern sports nutrition.
Keywords: Basketball, sports nutrition, energy balance, macronutrients, micronutrients, carbohydrates, proteins, fats, dehydration, electrolytes.